Specific PIP2 binding promotes calcium activation of TMEM16A chloride channels - Zhiguang Jia; Jianhan Chen (Communications Biology, 2021)
Chen and Jia investigate the synergistic regulating role of Ca2 + binding and the signaling lipid PIP2 in TMEM16A channel gating. Their study is significant as it provides new insights into the activated state of TMEM16A and highlights an example of functional importance of lipids in regulating membrane-associated proteins.